2021
DOI: 10.3389/fsurg.2021.757085
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Subtype of Non-small Cell Lung Cancer: Report of 159 Resected Pathological Stage I–IIIA Pulmonary Lymphoepithelioma-Like Carcinoma Cases

Abstract: Background: The current study analyzed resected stage I–IIIA pulmonary lymphoepithelioma-like carcinoma (LELC) cases to define the clinical characteristics, prognosis and long-term outcomes of resected LELC, with the purpose of guiding clinical management for this rare tumor.Methods: Resected stage I–IIIA LELC, adenocarcinoma (ADC) and squamous cell carcinoma (SCC) cases from our center were enrolled. Propensity score matching (PSM) was applied to minimize the selection bias. Overall survival (OS) and disease-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 33 publications
3
13
0
Order By: Relevance
“…The cohort comprised slightly more female patients than male patients. The female: male ratio was 1.07:1; the difference was not significant, which was consistent with most research reports 10,11 . However, a few studies reported the opposite ratio 12–14 .…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The cohort comprised slightly more female patients than male patients. The female: male ratio was 1.07:1; the difference was not significant, which was consistent with most research reports 10,11 . However, a few studies reported the opposite ratio 12–14 .…”
Section: Discussionsupporting
confidence: 87%
“…The female: male ratio was 1.07:1; the difference was not significant, which was consistent with most research reports. 10,11 However, a few studies reported the opposite ratio. [12][13][14] We supposed that it was because of the small number of patients enrolled in the studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations